POSSIBILITIES OF DIGITAL TECHNOLOGIES IN INCREASING THE EFFECTIVENESS OF PROFESSIONAL ACTIVITIES OF TEACHERS (Scientific journal of the Fergana State University, 2024)
In this article, the issues of widespread introduction of digital technologies in education in our country, the rational use of their capabilities to achieve the quality of education and the effectiveness of the professional activity of a teacher, as well as the issues of creating content that suits their education is becoming a requirement of the time, become relevant. A scientific assessment of the issue is also given by explaining the content of the concepts of digitalization, digital economy and digital technologies, and their definitions in dictionaries.